Microscale magnetic field modulation using rapidly patterned soft magnetic microstructures. Issue 55 (27th October 2021) - Shen, Fengshan; Yu, Yan; Li, Yuexuan; Feng, Hongtao; Wu, Tianzhun; Chen, Yan
Abstract : We present a simple, robust, and ultra-fast method to fabricate soft magnetic patterns for locally modulating magnetic fields. Abstract : The ability to locally modulate the magnetic field distribution is a prerequisite for efficient manipulation in magnetic force-based microfluidic devices. Here, we report a simple, robust, and fast fabrication method of magnetic microstructures for locally modulating magnetic fields. In the proposed method, a photosensitive magnetic composite consisting of carbonyl-iron microparticles in a poly(ethylene glycol) diacrylate (PEGDA) matrix was utilized to photolithographically fabricate magnetic microstructures. The magnetic behavior of the composite was first evaluated, and then various complicated patterns were fabricated on a glass slide within a few minutes. To demonstrate the capability of magnetic microstructures as a magnetic field concentrator, magnetic microstructures with different orientations to the external magnetic field were designed and fabricated, such as square arrays and grid-like magnetic microstructures. The modulated magnetic fields from such magnetic microstructures were numerically analyzed and then experimentally validated by trapping magnetic hydrogel beads. Further, the magnetically labeled cells were applied to the magnetic microstructures to prove the possibility of cell confinement via magnetic guidance in regions that exhibit enhanced magnetic field gradients. Overall, the proposed approach facilitates simple and fast fabrication of soft magnetic microstructures for microscale modulation of magnetic fields, which exhibits an immense application potential in magnetic force-based microfluidic techniques.